Physical Mobility Disorder in Patient Tn. S With Non-Hemorrhagic Stroke in Room A RS Iryou Houjin Aiwakai (Ikeda En) Okinawa Japan - Agelina Nur Kholifah; Siti Haniyah; Ikit Netra Wirakmi (LPPM Universitas Harapan Bangsa, 2024)
Non-hemorrhagic stroke is a major global health problem that causes disability and death. Non-hemorrhagic stroke is a major global health problem that causes disability and death. Based on the results of a pre-survey conducted on January 10 2023 at Houjin Aiwakai Hospital (Ikeda En), there were 10 patients who suffered from non-hemorrhagic stroke. These findings aim to describe the care of non-hemorrhagic stroke patients and physical disabilities at Iryou Houjin Aiwakai Hospital (Ikeda en), Okinawa, Japan. This study applies a descriptive method through a case study approach as an in-depth understanding of the nursing care process carried out. Data was collected through direct observation, interviews with medical staff patients. The research was conducted on one patient who experienced physical mobility problems on the right side. The findings after implementing nursing care within 3 days were that physical mobility problems improved, still complaining of difficulty moving the extremities a little. This research provides important insights for improving nursing practice and management of patients with stroke, as well as providing a reference in developing more effective care strategies.